(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the organizational factors that influence the development of information competence of preschool teachers. Using mixed methods, the study combines quantitative surveys of 287 preschoolers and qualitative interviews of 30 selected participants. The results show that institutional support and professional development are the most important indicators of information competence, followed by access to resources and organizational culture. Key themes identified include leadership responsibilities, continuous hands-on training, fair use of technology tools and collaboration, and the importance of an innovative environment.